2018
DOI: 10.3892/mmr.2018.8591
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of curcumin against cyclosporine A‑induced rat nephrotoxicity

Abstract: This study explored the potential value of curcumin, a natural product, in the protection of CsA‑induced nephrotoxicity. The aim of the present study was to investigate the effects of curcumin on Cyclosporine A (CsA)‑induced renal oxidative stress and determine the potential underlying molecular mechanisms of the renal protective effects of Cur. HK‑2 human renal cells were co‑treated with CsA and various doses of Cur. Cell survival rate was determined by an MTT assay, total cellular protein was collected and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
14
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 44 publications
(41 reference statements)
2
14
1
Order By: Relevance
“…In this study, ETEC challenge increased the fecal score (marking of the diarrhea) and impaired the spleen tissues. Moreover, the elevated serum concentrations of urea and crea indicated disruption of the kidney function in mice upon ETEC challenge [35,36]. The elevated serum concentrations of IL-6 and TNF-α indicating an acute inflammatory response in mice upon ETEC challenge.…”
Section: Discussionmentioning
confidence: 98%
“…In this study, ETEC challenge increased the fecal score (marking of the diarrhea) and impaired the spleen tissues. Moreover, the elevated serum concentrations of urea and crea indicated disruption of the kidney function in mice upon ETEC challenge [35,36]. The elevated serum concentrations of IL-6 and TNF-α indicating an acute inflammatory response in mice upon ETEC challenge.…”
Section: Discussionmentioning
confidence: 98%
“…[ 7–9 ] The role of inflammation and altered oxidative homeostasis in the pathogenesis of CsA induced organ dysfunction is further strengthened by the studies carried out in experimental models where agents exhibiting antioxidant and antiinflammatory properties have been shown to afford protection against such damage. [ 8,10–13 ]…”
Section: Introductionmentioning
confidence: 99%
“…In vitro studies examining the antioxidant effect of CRC showed promising results. An in vitro rat study demonstrated that renal toxicity due to cyclosporine decreased significantly by CRC administration and TOS and MDA levels in this group were significantly low 17 . Another animal study detected that in renal tissues of cisplatin and methotrexate administered rats MDA level was increased and GSH level was decreased; however in CRC administered rats level of oxidant MDA significantly decreased and level of antioxidant GSH significantly increased 18 .…”
Section: ■ Discussionmentioning
confidence: 99%